2019
DOI: 10.1007/s00223-019-00563-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Teriparatide Followed by Antiresorptive Therapy on Clinical Outcomes in Patients with Severe Spinal Osteoporosis

Abstract: Teriparatide (TPTD) is the most widely used anabolic agent in the treatment of patients with osteoporosis although its use is restricted in many countries. A recent randomised trial confirmed that TPTD was superior to risedronate at preventing vertebral fractures over a 2-year period. There is limited information on the relative effectiveness of TPTD compared with standard care in routine clinical practice. In this paper, we report the results of an extended observational study of 724 women referred to a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Teriparatide (TPTD) is the 1-34 fragment of parathyroid hormone. It has been successfully used for many years in the treatment of osteoporosis and has been found to be superior to bisphosphonates in the prevention of vertebral fractures in severe osteoporosis in observational studies (45). Moreover, TPTD was found to be superior to oral risedronate in preventing vertebral fractures in a double-blind randomized trial of individuals with severe osteoporosis (46).…”
Section: Bone Anabolic Agents In Osteogenesis Imperfecta Teriparatidementioning
confidence: 99%
“…Teriparatide (TPTD) is the 1-34 fragment of parathyroid hormone. It has been successfully used for many years in the treatment of osteoporosis and has been found to be superior to bisphosphonates in the prevention of vertebral fractures in severe osteoporosis in observational studies (45). Moreover, TPTD was found to be superior to oral risedronate in preventing vertebral fractures in a double-blind randomized trial of individuals with severe osteoporosis (46).…”
Section: Bone Anabolic Agents In Osteogenesis Imperfecta Teriparatidementioning
confidence: 99%
“…Although TPTD is more effective than oral bisphosphonates in this situation, there is greater burden for the patient in that the standard course of therapy involves daily self-administered subcutaneous injections for a 2-year period. Reflecting this fact, a previous audit based in the Edinburgh centre reported that 15.8% of patients who were offered TPTD therapy declined because they were unwilling to self-inject 18…”
Section: Discussionmentioning
confidence: 99%
“…For anabolic drugs like teriparatide and romosozumab we assumed that the reduction in risk of fracture during treatment would be sustained for 5 years as the result of follow-on treatment with antiresorptive medication. Although this has not yet been proven for romosozumab, observational studies suggest that the beneficial effects of teriparatide are sustained following introduction of antiresorptive therapy for at least 5 years [ 15 ].…”
Section: Methodsmentioning
confidence: 99%